Bulgarian private law at crossroads / Radosveta Vassileva. - Vassileva, Radosveta (Intersentia, 2022)
This book examines its fascinating and turbulent development from the end of the nineteenth century to the present day and highlights its distinctive features from a comparative perspective. Its main goal is to foster a better understanding of the current messy state of Bulgarian private law - particularly the law of obligations and property law - and an appreciation for its rich heritage. The book begins by reflecting on why the study of Bulgarian private law is worthwhile. Subsequently, the book provides an overview of the scattered sources of Bulgarian private law, since Bulgaria does not have a civil code. The author then explains the complex fabric of Bulgarian contract law which emerges from legislation, scholarly writing and case law, surveys the hazy realms of tort and unjust enrichment, and examines the fascinating transformations of the right to property which required the re-invention of property law twice over the past one hundred years. This is followed by a discussion on whether a reform of Bulgarian private law, including the enactment of a civil code, is necessary, as well as an evaluation of Bulgarian private law's preparedness to help tackle the challenges of the twenty-first century. Finally, the book explains, in context, literature for those willing to broaden their understanding of Bulgarian private law.